Icthyofaunal Diversity in Jagannath University New Campus Area, Keraniganj, Dhaka, Bangladesh - Asaduzzaman, Md; Raha Antu, Durjoy; Hossain, Md Sakhawat; Akbar, M Samrat; Biswas, Sajib; Ara Latifa, Gulshan (Bangladesh Journal of Zoology, 2023)
The study was carried out to know the ichthyofaunal diversity in Jagannath University new campus area from August 2020 to March 2021. A great variety of fish species were recorded from 15 diversified families. Among those, Cyprinidae was the most species-rich family, have 7 species. Total 29 fish species were identified; among them, the dominant order is Anabantiformes comprises of 9 species. Identified species mostly under least concern (20) category, Channa marulius (Hamilton, 1822) are the only endangered species, 1 species under vulnerable category, 4 species belong to near threatened. Three invasive species were recorded from this area, which is very alarming for native fish diversity. Gears and crafts were seen to: cast net, lift net, drag net, gill net, and chai, polo observed in the study area. Some pollution sources were also identified during the study period. Bangladesh J. Zool. 51(2): 165-173, 2023